Innovative Work Behavior pada Pegawai di DKI Jakarta: Pengaruh Learning Agility, Work Engagement, dan Digital Readiness - Anggarekso Alfadjri Riswan; Claresta Salsabila; Dinda Puspita Rani Mulya; Nopriadi Saputra (Penerbit Goodwood, 2021)
Purpose: This paper aims to examine innovative work behavior and the impact of learning agility, work engagement, and digital readiness on employees at DKI Jakarta. Research Methodology: This paper is based on the quantitative study by using a survey method through questionnaire distribution with 407 respondents of employees who work in DKI Jakarta. As for the data analysis technique, this analysis used SPSS with regression technique in simple regression. Results: This paper proves statistically there are significant and positive impacts from each variable (work engagement, digital readiness, and learning agility) on the innovative work behavior of employees in DKI Jakarta. Also, there are significant and positive impacts from each variable (work engagement and digital readiness) on learning agility. But learning agility does not have a role as an intervening variable in influencing the relationship between work engagement, digital readiness, and innovative work behavior. Limitations: This paper is using nonprobability sampling and also limited to employees who work in DKI Jakarta. Contribution: This paper shows how work engagement and digital readiness affect learning agility which has an impact on the innovative work behavior of employees in DKI Jakarta.